Development of integrated green halal supply chain model in food manufacturing industry - Aldeehani, Ahmaad Kadmouse (2019)
This project presents the development of integrated supply chain model in halal food manufacturing industry. The model has been integrated with accomplishment and consideration of green supply chain management (GSCM). Halal supply chain is one of most fundamental part in halal food manufacturing industries. The market of halal products is widely distributed throughout the world. There is global increase in the demand for halal products by Islamic countries as well as by non-Islamic countries. Halal food consumers are presently more alert and concern about the integrity of Halal status. Furthermore, they also curious about all the activities involved along the supply chain whether the products that they purchased were truly halal from the beginning to the end. The need of halal supply chain is crucial in ensuring that the concept of halal is not only applicable for the food itself but also for the whole supply chain starting from the farm to the customer. Due to the increasing concerns about environmental issues, many supply chain professionals include food supply chain find it necessary to understand the problems from system perspective rather than in single business entity. Green Supply Chain is then the attempt to measure, analyze and improve performance among various members to ensure that companies are operating in environmentally friendly manner. From the previous supply chain models and the current requirements includes environmental needs, this research project managed to develop an integrated halal food and green supply chain system that can be used by food manufacturers that are developing halal products for better productivity and quality. The identified supply chain components are human resources, process, environment, accreditations, logistics and traceability. These have been verified by food manufacturing companies in Malaysia and Kuwait. Finally, the framework of an integrated green halal supply chain model in food manufacturing industry has been developed successfully.